2011
DOI: 10.1111/j.1469-8749.2011.04126.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental impairment among infants born to mothers infected with human immunodeficiency virus and uninfected mothers from three peri-urban primary care clinics in Harare, Zimbabwe

Abstract: AIDS Acquired immunodeficiency syndrome ART Antiretroviral therapy BINS Bayley Infant NeurodevelopmentalScreener HIV Human immunodeficiency virus NDI Neurodevelopmental impairment PMTCT Prevention of mother-to-child transmission AIM The aim of this article is to document the risk of neurodevelopmental impairment (NDI) among infants enrolled in a programme for the prevention of mother-to-child transmission of HIV (human immunodeficiency virus) in Zimbabwe using the Bayley Infant Neurodevelopmental Screener (BIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…Not many other studies in sub-Saharan Africa with a similar age-range (Kandawasvika, et al, 2011;Drotar, et al, 1997;Boivin, et al, 1995;Msellati, et al, 1993) report this concern when comparing their HIV-infected group with the uninfected group.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Not many other studies in sub-Saharan Africa with a similar age-range (Kandawasvika, et al, 2011;Drotar, et al, 1997;Boivin, et al, 1995;Msellati, et al, 1993) report this concern when comparing their HIV-infected group with the uninfected group.…”
Section: Methodsmentioning
confidence: 94%
“…A recent study conducted in Zimbabwe (Kandawasvika, et al, 2011) found that the risk of neurodevelopmental impairment among HIV-exposed infected infants was double that among their non-infected peers (OR 2.1) when using the Bayley Infant…”
Section: )?mentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) infection in newborns, which is acquired during pregnancy, is linked with serious neurological problems. Although preventive measures are taken to prevent HIV infection in the fetus, perinatal exposure to HIV causes altered white matter microstructural integrity in uninfected neonates [187,188,189,190]. In addition, maternal hepatitis B and hepatitis C infection are associated with neurological outcomes [191].…”
Section: Infectionmentioning
confidence: 99%
“…Most studies of neurocognition in HIV-I children have been generalist in nature [i.e., focusing on a general developmental or IQ score, obtained from the Griffiths Mental Development Scales (GMDS), the Bayley Scales of Infant Development, the Kaufmann Assessment Battery for Children (K-ABC), or the Wechsler Individual Scales for Children (WISC; Eley et al, 2008; Shead et al, 2010; Kandawasvika et al, 2011; Laughton et al, 2012, 2013; Lowick et al, 2012)]. Such studies may miss more subtle deficits within specific cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results should be interpreted cautiously given the very wide age range of the sample (2–15 years). In another study, Kandawasvika et al (2011) investigated the risk of HIV-associated neurocognitive impairment in 65 HIV-I infants who were part of a Zimbabwean PMTCT program in primary healthcare clinics. They were compared to 188 HIV-EU and 287 HIV-UU infants.…”
Section: Introductionmentioning
confidence: 99%